(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
This study was designed to detect some genes associated with important virulence factors in streptococcus pyogenes . A total of 200 throat swabs were collected from patients suffering from pharyngitis from both sex and age from (1 - 15) years. carried out from ENT unit in Al-Hilla General Teaching Hospital and Al Noor Hospital during the period from January 2018 to December 2018 , Out of the 200 samples only 177 samples showed positive bacterial culture ,No growth was seen in other 23 samples ,The results indicate that the rate of Streptococcus pyogenes isolated from patient with pharyngitis is 30 ( 15%), others bacterial growth 147 ( 73%), and no growth 23 (12%). Molecular detection of virulence factor genes was done like M protein (emm) gene , the result shows that these genes were detected in all isolates bacteria (100%) with molecular length (914 bp) , SpeA gene was carried by using specific primer and it was found that (3.3%) isolates give positive result for this gene with amplicon (576 bp) , SpeB gene the result shows that (100%) isolates contain the gene with molecular length (952 bp) , SpeC gene also study by using specific primer at molecular length (405 bp) and the result s show that (75%) give positive results to this gene , the mac gene in all S.pyogenes isolates the results show that (30%) give positive , results to this gene with molecular length (389 bp) , scpA gene in all isolates the result shows that 17 isolates (56.6%) give positive result to this gene with amplicon size (622 bp)